2019
DOI: 10.1177/1558944719831333
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory Time–Related Hand Surgery Operating Room Inefficiency: A Systems Analysis

Abstract: Background: No study exists on preparatory time—from patient’s entrance into the operating room to skin incision—and its role in hand surgery operating room inefficiency. The purpose of this study was to investigate the length and variability of preparatory time and assess the relationship between several variables and preparatory time. Methods: Consecutive upper extremity cases performed for a period of 1 month by hand surgeons were reviewed at 3 surgical sites. Preparatory time was compared across locations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…Regarding the preparatory duration and variability, Milone et al's study discovered similar findings with Caggiano et al Specifically, they studied the preparation phase of hand-surgery cases, and they found that the mean preparatory time in 3 different surgical sites was 25.1 ± 8.1, 25.7 ± 9.4, and 20.7 ± 8.3 min, respectively [20]. The authors concluded that increased variability signifies a poorly designed process that has room for improvement in the workflow [8].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Regarding the preparatory duration and variability, Milone et al's study discovered similar findings with Caggiano et al Specifically, they studied the preparation phase of hand-surgery cases, and they found that the mean preparatory time in 3 different surgical sites was 25.1 ± 8.1, 25.7 ± 9.4, and 20.7 ± 8.3 min, respectively [20]. The authors concluded that increased variability signifies a poorly designed process that has room for improvement in the workflow [8].…”
Section: Discussionsupporting
confidence: 53%
“…Milone et al [20] also identified that the cases with surgeons with more years of experience had lower preparatory duration which is likely due to the fact that their surgeons were present for a high percentage of the preparatory duration in the OR. However, this contrasts our experience where the surgeon was present mainly for the positioning of the patient at the end of the preparatory phase which is the reason we did not elect to use the surgeon experience as a confounder in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…I risultati ottenuti sono stati comparati con la letteratura e risulta evidente come il management dei tempi operatori sia un punto cardine nell'organizzazione del blocco operatorio. In relazione ai tempi pre operatori i dati analizzati non sono del tutto in linea con gli studi pubblicati, infatti al Langone Orthopedic Hospital di New York (USA) il tempo pre operatorio è risultato essere di 24,4 minuti [13] (per loro considerato inefficiente essendo il 34% del tempo totale in sala operatoria), il tempo però non variava in base alla tipologia di intervento ma a seconda del chirurgo o del tipo di anestesia. In relazione ai tempi post operatori invece i risultati si allineano con la letteratura, basti pensare ai 31,09 minuti [14] del tempo di turnover per interventi di Otorinolaringoiatria all'Hospidal Colorado (USA), ai 42,8 [15] minuti del tempo di turnover per interventi eseguiti al MetroHealth Medical Center di Cleveland in Ohio (USA) ridotti a 26,4 minuti dopo alcune modifiche apportate alla pianificazione del processo multidisciplinare, ai 41 minuti [16] di mediana del tempo di turnover per interventi eseguiti all'University Children's Hospital di Loma Linda California (USA) diminuiti a 32 minuti dopo la riprogrammazione delle sale operatorie (che dimostra come modificare i processi multidisciplinari può migliorare significativamente l'efficienza in un ospedale) o infine ai 53 minuti [17] del tempo di turnover per interventi eseguiti all'IRCCS Istituto Ortopedico Galeazzi di Milano nel 2020 durante la pandemia.…”
Section: Discussioneunclassified
“…However, there has been surprisingly little innovation in the elbow positioning marketplace in the last several decades. Surgical procedural inefficiency and variability in operative time for orthopaedic surgical procedures have been highlighted in the literature recently (DeCook and Statton 2022;Milone et al 2019). Early in my career, I performed elbow arthroscopy with patients in the lateral decubitus, prone, and even supine suspended positions.…”
Section: Introductionmentioning
confidence: 99%